(untitled) (Fiep Bulletin - online, 2016)
This study aimed to check and evaluate the nutritional status of special students from the Neurological Adaptation Centre “Nosso Canto”, in the city of Foz do Iguassu / PR, Brazil, checking and evaluating their weight and height, and then perform an individual and collective nutritional assessment of the students. A field, descriptive and transversal research, with a sample of 91 subjects (53 men and 38 women), aged between 5 and 35 years. The sample was divided into 2 different groups: children - 67 students aged 5 to 17 years, and adults - 24 students aged 18 to 35, for the purposes of evaluation protocols for the nutritional status. All surveyed students weight and height were measured, in order to assess their nutritional status by the Body Mass Index (BMI); for the adults group, the waist circumference was also measured. The BMI results showed that 48% of respondents (n = 44) were classified as a normal weight - within the normal range; 42% (n = 38) were classified as overweight; and 10% were classified as below the normal weight (n = 9). For the waist perimeter evaluation on the adult group, there was a prevalence of 52% for no imminent cardiovascular risk and metabolic diseases, according to the reference table proposed by the World Health Association (WHO, 1998); 26% of the sample showed an increased risk, and 22% showed a highly increased risk. Therefore, the study concluded that a multidisciplinary professional intervention for special students is essential, especially from dietitians and Physical Education professionals, in order to improve the quality of the students’ diet and energy balance.